Strategi Promosi Sabun Lux di Jawa, 1929-1941 - Putri, Amanda Lathifah Laksmana; Sunarti, Linda (Jurnal Sejarah Indonesia, 2023)
This article discusses the history of the development of Lux soap promotion strategy in Java in the period 1929-1941. Lux is one of the soap product variants produced by the Unilever company. The first promotional effort of Lux Soap took place in 1929 and continued until 1941. With the aim of increasing sales profits, Lux products were then intensively promoted through various forms of advertisements. The variety of advertisements displayed included different visual aspects, promotional strategies, and language usage. In this article, the development of advertisements and marketing strategies of Lux soap along with their impacts, both in terms of sales and social impacts, are presented. The writing of this article uses the historical method, by collecting sources such as newspapers, magazines, and books from the collections of the National Library, UI Library, and online sources. The results showed that Lux's promotion strategy, which was widely spread in various media, including local and national newspapers, caused an increase in sales and popularity of Lux products. In addition, Lux's promotional strategies such as holding contests also proved to have a significant impact on the sales of the product.